2022
DOI: 10.3390/machines10070574
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanical Knee Supporter Device for Shock Absorption

Abstract: Conventional knee supporters generally reduce knee pain by restricting joint movement. In other words, there were no mechanical knee supporters that functioned powerfully. Considering this problem, we first devised a device in which a spring is inserted into the double structure of the cylinder and piston, and a braking action is applied to the piston. This mechanism retracts when the knee angle exceeds a certain level. Next, the knee and the device were modeled, and the dynamic characteristics of the device w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In other words, it is desirable to install a mechanism with a damper at an intermediate position between the bar and the shoulder. Similarly, it has been found that the load on the ankle and knee joints can also be reduced by increasing the damping factor, (9,10) which suggests that the model based on shock absorbers is applicable to the human physiology.…”
Section: Reducing the Load On The Shoulder (Elastic Constant And Damp...mentioning
confidence: 89%
See 1 more Smart Citation
“…In other words, it is desirable to install a mechanism with a damper at an intermediate position between the bar and the shoulder. Similarly, it has been found that the load on the ankle and knee joints can also be reduced by increasing the damping factor, (9,10) which suggests that the model based on shock absorbers is applicable to the human physiology.…”
Section: Reducing the Load On The Shoulder (Elastic Constant And Damp...mentioning
confidence: 89%
“…There are multiple examples of muscle utilization that combine control engineering and ergonomics. (9,10) In this study, we demonstrated the basic structure and mechanisms of the device, analyzed the dynamic properties of certain mechanisms, and developed effective mechanical elements to lift the load. We also conducted experiments to faithfully reproduce the concept of the lifting technique.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a simple rst-order delay control system is modeled by simulating the lifting motion of an object by a martial artist. Examples of applications of the hidden power of martial arts already exist in the eld of shock absorption and other areas, but to the authors' knowledge, none are known that are limited to lifting objects [13,14]. The simpli ed object lifting method in this paper could be applied to simpli ed lifting actions of objects in agricultural work and nursing care.…”
Section: Introductionmentioning
confidence: 99%